2011
DOI: 10.1007/s12020-011-9548-0
|View full text |Cite
|
Sign up to set email alerts
|

The source of leptin, but not leptin depletion in response to food restriction, changes during early pregnancy in mice

Abstract: Maternal food restriction during pregnancy results in adverse consequences for offspring, including obesity and cardiovascular disease. Early pregnancy is a critical period for this programming effect. Leptin is a regulator of energy homeostasis that also affects placental and fetal development. As food restriction results in decreased serum leptin levels, at least in non-pregnant animals, leptin depletion may be one mechanism by which food restriction affects development. The goal of this study was to test wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
10
2
Order By: Relevance
“…Concomitantly, plasma leptin concentrations did not decline in any of the groups in our study, opposite to previous works in rabbit [37], mouse [51, 59] and sheep [55]. We hypothesize that the absence of differences in our study may be explained by different facts.…”
Section: Discussioncontrasting
confidence: 99%
“…Concomitantly, plasma leptin concentrations did not decline in any of the groups in our study, opposite to previous works in rabbit [37], mouse [51, 59] and sheep [55]. We hypothesize that the absence of differences in our study may be explained by different facts.…”
Section: Discussioncontrasting
confidence: 99%
“…In a further study, in mice restricted to 50% of their normal food consumption from day 0.5 to 11.5 of pregnancy, serum leptin concentration declined signifi cantly (Schlitt and Schulz 2012). In sheep, food restriction prevents the increase in serum leptin that occurs during normal pregnancy aft er 12 h of fasting in hyperemesis gravidarum (Bispham et al 2003).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, moderate physical training (50-70 % VO 2max ) results in negative energy balance and potentiates the thermic eff ects of food in lean subjects and this response may be enhanced in the obese [ 9 ] . In humans, male adolescents showed an enhanced lean muscle mass and prevention of body weight gain in response to aerobic exercise (12 weeks, 65-85 % maximum heart rate) [ 22 ] . In the present study, LP+T animals showed a reduced gain of body weight during the weeks of moderate physical training.…”
mentioning
confidence: 99%